PENGELOLAAN FARMASI DAN WAKTU TUNGGU OBAT DI RUMAH SAKIT: SYSTEMATIC LITERATURE REVIEW - Prima Aprianti; Helen Andriani (LPPM Universitas Awal Bros, 2026)
Pharmacy waiting time is a key indicator in evaluating hospital service quality. The waiting time is influenced by various pharmacy management factors, such as stock systems, distribution flow, and information systems. This study aims to identify the relationship between pharmacy management and pharmacy waiting time in hospitals based on a systematic literature review. A systematic review was conducted using ProQuest database within the last ten years, screened through duplication removal, title, abstract, and full-text assessment. A total of 772 articles were identified, and after strict selection, 8 articles met the inclusion criteria for analysis. Key factors affecting waiting time include prescription input delay, drug availability, doctor confirmation, prescription copy making, and stock management. Management interventions such as Six Sigma, Lean Thinking, Root Cause Analysis (RCA), automated queue technology, and integrated information systems were proven effective in reducing waiting time and improving patient satisfaction. Effective pharmacy management significantly reduces waiting time and increases patient satisfaction. Strengthening information systems, stock management, workflow improvement, and continuous application of quality management methods are required.